Optimized Processing Techniques for Enhancing Fillet Yield from Low-Value Fish in Lamongan, East Java, Indonesia - Choirul Anam; Damat Damat; Roy Hendroko Setyobudi; Ida Ekawati; Praptiningsih Gamawati Adinurani; Shazma Anwar; Rusli Tonda; Wahyu Mushollaeni; Mohammad Taufiq Shidqi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Fishing activities often yield a bycatch of low-value fish (trash fish) that typically remains underutilized. This study aimed to identify the most effective preparation technique to improve the physical and chemical quality of fillets from three types of trash fish: Orangefin ponyfish (Leiognathus bindus), chacunda gizzard shad (Anodontostoma chacunda), and sardine (Sardinella fimbriata). A Randomized Block Design (RBD) was used with two factors: fish species and preparation technique, including mechanical treatment, blanching, immersion in 1% acetic acid, and immersion in 1% papain enzyme. Data were statistically analyzed and presented descriptively in tables and graphs. The results showed that treatment with 1% papain enzyme yielded the highest fillet yield (47.5% to 63.2%) and the shortest processing time. Additionally, the enzymatic treatment produced fillets with favorable chemical characteristics: moisture content (77.46% to 80.13%), protein (7.39% to 9.29%), fat (8.01% to 9.49%), and ash (1.55% to 2.83%). This study demonstrates that enzymatic preparation is effective in enhancing both the efficiency and quality of trash fish fillets, potentially increasing the added value of fishermen's catches.